GRANDES TAXONES DE FITOBENTOS Y SU RELACIÓN CON LA HIDROLOGÍA, FÍSICA Y QUÍMICA DE PEQUEÑOS RÍOS ANDINOS (2004)
In 16 sampling points, which were located in 14 streams of the middle and high basin of the Bogotá River (2.617 - 2.988 m), we analyzed some physical, chemical and hydrological variables and the benthic algae community (taxonomic classes). By means of Principal Component Analysis, we concluded that the rivers respond to a basin area gradient and mineralization gradient. The streams are of the acidic order 1-4, and their flow rates are lower than 3.7 m3 s-1. The total nitrogen and total  phosphorus concentrations are lower than 7 mg l-1 and 1.4 mg l-1,  respectively. The benthic community is dominated by diatoms,  cyanobacteria and green algae. The basin area and mineralization gradients determine the dominant and co-dominant benthic algae class per stream.